Design Of Time Estimation System In Manufacturing Products On Cnc Machinery With Process Approach - Sudirman, Agus (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2023)
This research was conducted at the Industrial Service Unit of the University of Muhammadiyah Surakarta, which is a Service Unit engaged in the machinery industry, with a Make To Order-based production system. The current state of product completion time orders are made based on estimates only. In this study, a decision support system was designed to calculate product time estimates, change manual calculations or estimates with computer calculations. The calculation refers to product specifications and cutting tools used, where these two things are used to calculate the length of a machining process. In addition, the machine load, the time to order raw materials, the availability of working drawings, and the efficiency of the machine used are also considered. Based on the results of the implementation in the case of the RAGUM-TI product, the completion time was 6331.28 minutes or 106 hours, and the product could be completed in 16.5 days with 80% machine efficiency and 8 hours of work per day. With the decision support system produced in this study, it can increase the speed and accuracy of the estimation process by the company.